Stability of paracetamol instant jelly for reconstitution: Impact of packaging, temperature and humidity - Almurisi, Samah Hamed; AL-japairai, Khater Ahmed Saeed; Alshammari, Farhan; Alheibshy, Fawaz; Sammour, Rana M.F.; Doolaanea, Abd Almonem (MDPI, 2022)
The stability of the medicinal product is a major concern in the pharmaceutical industry and health authorities, whose goal is to guarantee that drugs are delivered to patients without loss of therapeutic properties. This study aims to evaluate the effect of environmental conditions and packaging on the stability of paracetamol instant jelly sachets based on both chemical and physical stability. The paracetamol instant jelly was packaged in plastic sachets (packaging 1) and sealed aluminium bags in screw-capped amber glass bottles (packaging 2), which were stored in real-time and accelerated stability chambers for 3 months. Samples were taken out from the chambers and were characterised for appearance, moisture content, texture, viscosity, in vitro drug release, paracetamol content, and 4-aminophenol level at different time points. The real-time storage condition at a lower temperature maintained the stability of the paracetamol instant jelly, while the accelerated condition led to a significant change in the formulation properties. In addition, the proper packaging of paracetamol instant jelly maintained the paracetamol’s stability, regardless of environmental conditions, for three months. The results show that the environmental conditions and packaging play a significant role in maintaining paracetamol instant jelly stability.